Combined Soil Inoculation with Mycorrhizae and Trichoderma Alleviates Nematode-Induced Decline in Mycorrhizal Diversity - Covacevich, Fernanda (2025)
Arbuscular mycorrhizal fungi (AMF) and Trichoderma spp. (T) are known as plant-beneficial fungi effective against root-knot nematodes, but their interactions in the rhizosphere are not well understood. This study examined how Meloidogyne javanica influences AMF colonization and community diversity at the root-soil interface of tomato plants. A 60-day growth chamber experiment was conducted with tomato plants grown in non-sterile agricultural soil, either infected or not with M. javanica, that received a single inoculation with AMF or Trichoderma (strains T363 or TJ15), combined AMF + T inoculations, or no inoculation (Control). Both single and combined inoculations significantly reduced root galls, eggs, and soil nematode larvae. An AMF community analysis via single-strand conformation polymorphism of the D1 region of 28S rDNA gene (Glomeraceae family) revealed that M. javanica decreased AMF diversity and altered community structure, in plants single-inoculated with AMF. However, a combined inoculation with Trichoderma appears to prevent this reduction and maintain AMF diversity. While M. javanica reduced root mycorrhizal colonization, it did not affect Trichoderma abundance. These results suggest that Trichoderma may be more resilient to nematode infection, helping stabilize AMF communities and enhance biocontrol. Thus, combining AMF and Trichoderma inoculations could better preserve root health and improve biological control effectiveness against M. javanica.